Peningkatan Kemampuan Mahasiswa Bahasa Inggris FKIP UNRI Dalam Mengidentifikasi Elemen-Elemen Plot Dalam Drama Pendek Melalui Pembelajaran Kooperatif Tipe Group Investigation - Jismulatif '; Syafri. K (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
The objective of this research was to know whether the method of Group Investigation couldimproved the ability of the fourth semester students of English Department, FKIP UR, in identifyingthe elements of plot in short drama (one act drama). This research was also aimed to find what factorscaused the improvement.The research method used was the Classrom Action Research (CAR). Throughthe application of Group Investigation, the research findings showed that the ability of the fourthsemester students of English Department has improved significantly in identifying the theme and theelements of plot in short drama text. Average percentage of students’ activity in meeting I (56.05%)increased to (67.42%) in meeting II in cycle I. This percentage increased to (84.04%) in meeting I incycle II. The improvement of percentage activity became (90.90%) in meeting II cycle II. The averagegrade of students’ ability in pre-test was (54%) after students involvement in teaching and learningprocess by using the type of Group Investigation, the students’ ability became (61.88%) in post-test Iand reached (78.18%) in post-test II.The dominant factors that cause the students’ improvement are 1)alomost all students were active in teaching and learning process 2) the students were struggle hard andresponsible to their own group.